Analisis Wacana Kritis Model Teun A.Van Dijk pada Surat Kabar Online dengan Tajuk Kilas Balik Pembelajaran Jarak Jauh Akibat Pandemi Covid-19 - Mukhlis, Muhammad; Masjid, Akbar Al; Widyaningrum, Heny Kusuma; Komariah, Kokom; Sumarlam, Sumarlam (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2020)
This study aimed to describe the Teun A Van Dijk's model text's dimensions in online news text discourse on Kompas.com Newspaper with the headline